1992
DOI: 10.1016/0378-1135(92)90032-o
|View full text |Cite
|
Sign up to set email alerts
|

Immune mechanisms in the pathogenesis of viral diseases: a review

Abstract: Three immunopathological mechanisms may determine the pathogenesis of viral diseases in animals. (1) A variety of viruses causes transient or prolonged immunosuppression by infecting lymphoreticular tissues and interacting with components of the immune system. (2) In persistent viral infections effective immune responses may result in tissue damage. The mechanisms involved are T-cell-mediated destruction of infected cells and delayed-type hypersensitivity. (3) In a number of viral diseases pathogenic immune co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…This agrees with the findings of other workers (Rao and Rao, 1992;El-Yuguda, 2000) who observed significant depression of primary antibody of chickens to ND vaccine when administered one week after IBD infection or vaccination. Trautwein (1992) also reported that chickens infected with IBD virus become susceptible to opportunistic secondary infections and respond poorly to immunization against other pathogens. This could be due to the effect of the virus on the lymphoid organs, such as the bursa of Fabricious of the infected birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with the findings of other workers (Rao and Rao, 1992;El-Yuguda, 2000) who observed significant depression of primary antibody of chickens to ND vaccine when administered one week after IBD infection or vaccination. Trautwein (1992) also reported that chickens infected with IBD virus become susceptible to opportunistic secondary infections and respond poorly to immunization against other pathogens. This could be due to the effect of the virus on the lymphoid organs, such as the bursa of Fabricious of the infected birds.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the village poultry setting where chickens and other birds like the guinea fowls are raised together feeding and roosting in the same place, they could serve as source of infection to each other (Soniaya, 1999). Besides the immunosuppressive effects of IBD has been well documented (Lukert, 1992;Trautwein, 1992;ElYuguda, 2000). This paper describes the interference of IBD virus or vaccine with the immune response of guinea fowls to Newcastle disease "LaSota" vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, organ pathology occurs as a direct consequence of the intrinsic ability of many viruses to destroy their cellular targets and is usually intensified by inflammatory cells recruited to sites of infection by chemokines released by infected cells (18,69,75). However, this paradigm is not universal, and several studies have indicated a significant role for antigen-specific T cells in organ pathology.…”
mentioning
confidence: 99%
“…In Table I, a compilation is presented of Chisari andFerrari (1995) Hanke et al (1995) Zinkernagel and Hengartner (1994) Zaki et al (1995) Miller and Karpus (1994) Fleming et al (1993 Mokharian and Swoveland (1987) Johnson et al (1978) Doymaz and Rouse (1992) Narayan and Clements (1989) Alwan et al (1993) Kurane and Ennis (1994) Trautwein (1992) a These are good source references and are not meant to reflect the primary discoveries of the phenomenon. Removing infected cells usually engenders some tissue damage because of a concomitant inflammatory response, but this is not an unreasonable price to pay to control infection by highly cytolytic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The latter phenomenon probably accounts for the pathogenesis of dengue hemorrhagic fever (DHF) (Kurane and Ennis, 1994) and coronavirus-induced infectious peritonitis, a common viral disease in the domestic cat (Trautwein, 1992). However, there are at least two widely accepted examples in which humoral mechanisms account for the immunopathogenesis of viral lesions.…”
Section: Immune Inflammatory Responses Invoixinc: Antihodymentioning
confidence: 99%